Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð¼Ð°Ð»Ñ‹Ñ… Ð´Ð¾Ð· Ð¾Ð·Ð¾Ð½Ð° Ð½Ð° Ð³Ð¸Ð¿ÐµÑ€Ñ‚Ð¾Ð½Ð¸Ñ‡ÐµÑÐºÐ¸Ð¹ Ð»Ð¸Ð·Ð¸Ñ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² - Belykh, I. A.; Volovelskaya, I. L.; Zinchenko, V. D. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
There was registered the dynamics of erythrocyte hemolysis in hypertonic solutions with 0.25, 0.45, 0.85, 1 and 2 M NaCl content at 4Â°C within 8 days when adding ozone in 0.16, 0.32 and 0.48 mg/l dose into the medium. In the media, containing ozone in 0.16 mg/l dose the erythrocyte hemolysis increased slower, than in those with similar NaCl concentrations free of ozone additives. After erythrocyte freeze-thawing in â€œPropandiosakharolâ€ cryoprotective medium there was observed the hemolysis delay when introducing 0.16 mg/l ozone into the thawed cell suspension. Results are explained with modifying the erythrocyte membrane under low ozone dose effect.